The Influence of Work Period and Work Location of Workers with Understanding of Corporate Life Saving Rules (CLSR) at Oil and Gas Fuel Terminal Companies in Indonesia - Clint Devan Yogama; Desti Azhari; I Made Dwi Darmaputra (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Knowledge is something that is owned by employees as a condition to be able to complete work, therefore better knowledge will lead to increased performance. In this study, the author uses a research design for education, dissemination and information to workers in the field by applying corporate life saving rules with periodic intervention using a cross-sectional study, namely the measurement of data on independent variables (location of work and years of service). and bound (knowledge of corporate life saving rules) only once at a time. The results of the study stated that there was a relationship between tenure and work location on the knowledge of corporate life saving rules (CLSR) workers with a P-value less than 0.05, so that it was concluded that there was a relationship between tenure and understanding of corporate life saving rules (CLSR) with The results show that workers with 1-5 years of service have a better level of understanding than workers with 6-10 years of service. Apart from working period, there is also a relationship between work location and understanding of corporate life saving rules (CLSR). Workers who work at the work site (site) have a better level of understanding than office workers. Overall, the level of understanding of workers on corporate life saving rules (CLSR) at fuel oil and gas terminal companies in Indonesia with a "good" level of understanding reached 50.3%, while workers who needed "improvement" in understanding reached 49.7%. These results indicate the need for education, dissemination and information through further periodic interventions to all workers, both in field locations and in offices. Abstrak: Pengetahuan merupakan sesuatu yang dimiliki oleh karyawan sebagai syarat untuk dapat menyelesaikan pekerjaan, oleh karena itu pengetahuan yang semakin baik akan menyebabkan peningkatan kinerja. Dalam penelitian ini, penulis menggunakan desain penelitian edukasi, diseminasi dan informasi kepada pekerja di lapangan dengan penerapan corporate life saving rules dengan intervensi secara berkala dengan menggunakan studi potong lintang (cross sectional study) yaitu pada pengukuran data variabel bebas (lokasi kerja dan masa kerja) dan terikat (pengetahuan corporate life saving rules) hanya satu kali dalam satu waktu. Hasil penelitian menyatakan bahwasanya ada hubungan antara masa kerja dan lokasi kerja terhadap pengetahuan pekerja corporate life saving rules (CLSR) dengan nilai P-value0,05, sehingga didapatkan kesimpulan terdapat hubungan antara masa kerja dengan pemahaman corporate life saving rules (CLSR) dengan hasil bahwa pekerja dengan masa kerja 1-5 tahun memiliki tingkat pemahaman yang lebih baik daripada pekerja yang memiliki masa kerja 6-10 tahun. Selain masa kerja, juga terdapat hubungan antara lokasi kerja dengan pemahaman corporate life saving rules (CLSR). Pekerja yang bekerja di lokasi kerja (site) memiliki tingkat pemahaman yang lebih baik dibandingkan dengan pekerja kantor (office). Secara keseluruhan, tingkat pemahaman pekerja terhadap corporate life saving rules (CLSR)  di perusahaan terminal bahan bakar minyak dan gas di indonesia dengan tingkat pemahaman “baik” mencapai 50.3%, sedangkan pekerja yang membutuhkan “peningkatan” pemahaman mencapai 49,7%. Hasil tersebut menunjukkan perlunya edukasi, diseminasi dan informasi melalui intervensi berkala lebih lanjut kepada seluruh pekerja baik di lokasi lapangan maupun di perkantoran.